ANALISIS PENGUASAAN KATA DEPAN â€œGEIâ€ DAN â€œGENâ€ PADA MAHASISWA ANGKATAN 2017 PENDIDIKAN BAHASA MANDARIN - Sari, Beliya Fatika; Thamrin, Lily; Khiong, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractPreposition is one of the important parts of speech in Mandarin language. â€œgeiâ€ and â€œgenâ€ are indicated as an object of preposition. These two words are often used in a daily conversation. The use of them has similarity and difference. Hence, the Mandarin learners who learn these two words frequently experience some mistakes in comprehending which this could cause the incorrect use based on its situation.In order to find out thestudentsâ€™ preposition mastery of Mandarin Education Program FKIP UNTAN to words the words of â€œgeiâ€ and â€œgenâ€, the writer used analysis methodology to know the studentsâ€™ mastery and analyze the studentsâ€™ difficulties towards the use of preposition â€œgeiâ€ and â€œgenâ€.Â  The result shows that the studentsâ€™ preposition mastery towards the word â€œgeiâ€ was better than the word â€œgenâ€. The percentage of the answers â€œgeiâ€ reached 62% while the word â€œgenâ€ reached 59%.Â  In the analysis of the types of difficulties, the writer found the diction as particular errors which were often madeby the students.Â Keywords: Preposition,Â  Gei Gen, Mastery Condition